Decoding power dynamics and hidden ideologies in Kenya’s gender equality policies - G.E. Aberi (Язык и текст)
This paper examines Kenya's gender policy discourse using Critical Discourse Analysis to unravel themes and power dynamics influencing gender equality efforts. Despite notable advancements in promoting gender equality and empowering women, obstacles remain in achieving equitable relationships between men and women across various domains of life. This study addresses three key questions: (1) what are the dominant themes within Kenya's gender policy for the last three decades? (2) How do hidden ideologies and power structures influence these themes? and (3) how do these themes reflect and sustain imbalanced power dynamics between men and women within the Kenyan society? Recognizing a research gap in the existing literature concerning the recurring themes and intersection of language use and gender policies in Kenya. Using Norman Fairclough’s Three-Tier Approach to Critical Discourse Analysis, the study analyzes ten publicly available policy documents published between 1994 and 2024 by the Kenyan government, NGOs, and UN organizations focused on women's rights to gender equality. The findings indicate that though official policy texts are framed in ways that support the need for gender equality policies in Kenya, contradictions still abound regarding the prevailing hidden ideologies and power dynamics that influence gender-related policies and practices. In light of these findings, the paper concludes by suggesting directions for future research, including longitudinal studies to assess the impact of changing discourses on actual gender equality outcomes in Kenya.